Examining the potential for climate change mitigation from zero tillage - Mangalassery, S.; Sjögersten, Sofie; Sparkes, D.L.; Mooney, Sacha J. (Cambridge University Press, 2015)
The benefits of reduced and zero-tillage systems have been presented as reducing runoff, enhancing water retention and preventing soil erosion. There is also general agreement that the practice can conserve and enhance soil organic carbon (C) levels to some extent. However, their applicability in mitigating climate change has been debated extensively, especially when the whole profile of C in the soil is considered, along with a reported risk of enhanced nitrous oxide (N2O) emissions. The current paper presents a meta-analysis of existing literature to ascertain the climate change mitigation opportunities offered by minimizing tillage operations. Research suggests zero tillage is effective in sequestering C in both soil surface and sub-soil layers in tropical and temperate conditions. The C sequestration rate in tropical soils can be about five times higher than in temperate soils. In tropical soils, C accumulation is generally correlated with the duration of tillage. Reduced N2O emissions under long-term zero tillage have been reported in the literature but significant variability exists in the N2O flux information. Long-term, location-specific studies are needed urgently to determine the precise role of zero tillage in driving N2O fluxes. Considering the wide variety of crops utilized in zero-tillage studies, for example maize, barley, soybean and winter wheat, only soybean has been reported to show an increase in yield with zero tillage (7·7% over 10 years). In several cases yield reductions have been recorded e.g. c. 1–8% over 10 years under winter wheat and barley, respectively, suggesting zero tillage does not bring appreciable changes in yield but that the difference between the two approaches may be small. A key question that remains to be answered is: are any potential reductions in yield acceptable in the quest to mitigate climate change, given the importance of global food security?